2019
DOI: 10.5539/jas.v11n10p121
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Nutritious Drought Tolerant Maize Adoption and Mineral Fertilizer Application Under Smallholder Farm Conditions in Ghana

Abstract: The study sought to examine adoption of nutritious drought tolerant (DT) maize using social science research methods and participatory demonstration trials. The social science study used mixed method approach which combined both qualitative and quantitative methods. A split-plot demonstration trial of three improved maize varieties and a local variety, and two levels of Nitrogen fertilizer were established. The two fertilizer levels were low N [LN] (30 kg N ha-1) and high N [HN] (90 kg N ha-1). The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, using low N fertilization (30 kg N ha −1 ) and 46 kg ha −1 of superphosphate. Yeboah et al (2019) observed no significant effect of DT varieties and nitrogen fertilizer in farm conditions during the major and minor seasons. Kabate et al (2015), by reviewing the factors driving the doubling of maize yields in recent years in Ethiopia, showed that this was due to the adoption of modern (tolerant and high yielding) varieties coupled with the application of a small amount of nitrogen (34 kg ha).…”
Section: Efficiency Of Fertilizer Microdosing Across Different Dt Mai...mentioning
confidence: 71%
See 1 more Smart Citation
“…However, using low N fertilization (30 kg N ha −1 ) and 46 kg ha −1 of superphosphate. Yeboah et al (2019) observed no significant effect of DT varieties and nitrogen fertilizer in farm conditions during the major and minor seasons. Kabate et al (2015), by reviewing the factors driving the doubling of maize yields in recent years in Ethiopia, showed that this was due to the adoption of modern (tolerant and high yielding) varieties coupled with the application of a small amount of nitrogen (34 kg ha).…”
Section: Efficiency Of Fertilizer Microdosing Across Different Dt Mai...mentioning
confidence: 71%
“…The use of such improved maize varieties can help farmers to produce maize during the drought periods, especially when the drought occurs at the crucial crop development stages such as the flowering and grain filling stages. Their climatic endurance, highest yield, and grain quality were the strong points of their adoption (Yeboah et al, 2019). Varieties of DT maize are expected to improve the resilience of maize-based farming systems in Benin by enhancing food security, nutrition and farmer's income, and reducing poverty (Makate et al, 2017;Wossen et al, 2017;Abdoulaye et al, 2018;Lunduka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have investigated this subject in Ghana, mainly looking at the relationship between fertilizer adoption and crop yield [38][39][40][41][42]. Other studies have focused on the determinants of fertilizer (especially chemical fertilizer) adoption [43][44][45]. Tis study expands the scope to examine the impact on farm income, gross margins, and its commercialization potential in Ghana.…”
Section: Introductionmentioning
confidence: 99%